Close circuit television camera applications in Abu Dhabi United Arab Emirates: surveillance system effectiveness assessment - Salem Al Neyadi, Ali Hamad (2021)
Closed-circuit television (CCTV) cameras are intensively used in Abu Dhabi to maintain surveillance for ensuring law enforcement and helping with crime control at public places. However, there are challenges regarding CCTV cameras, such as limited knowledge of CCTV functioning and improper understanding of several stakeholders towards the maintenance of public safety. Therefore, the current study aimed to identify the factors that impact CCTV effectiveness in the United Arab Emirates (UAE). The study has two objectives. The first objective was to identify the factors related to CCTV effectiveness. The second objective aimed to investigate the impact of the identified factors on the effectiveness of the surveillance management system. This study used a case study from city surveillance management in Abu Dhabi. It surveyed 250 integrators that qualified to install CCTV across the city of Abu Dhabi with a valid response of 196. The findings showed that the three factors (Authority monitoring and control, Government CCTV standards, and CCTV integrators) have a significant impact on the effectiveness of the surveillance management system. The highest level of correlation was found between CCTV effectiveness and government CCTV standards. This can be understood by the notion that the role of Authority control and monitoring using CCTV shows that Abu Dhabi monitoring & control centre standard provides clear guidance to integrators. The finding confirmed that timely response from the Abu Dhabi monitoring & control centre for any technical clarification and the standards provided by the authority increases CCTV effectiveness. The study proposes a smart city surveillance system to electronically monitor the important cities in UAE and the entire nation.